Skip to content
Related Articles

Related Articles

Improve Article
GATE | GATE-CS-2017 (Set 1) | Question 18
  • Last Updated : 22 Sep, 2017

The statement (¬ p) → (¬ q) is logically equivalent to which of the statements below?

I. p → q

II. q → p

III. (¬ q) ∨ p

IV. (¬ p) ∨ q
(A) I only
(B) I and IV only
(C) II only
(D) II and III only


Answer: (D)

Explanation: Given,



(¬ p) → (¬ q)
= ¬ (¬ p) ∨ (¬ q) { since x → y = ¬ (x) ∨ y }
= (¬ ¬ p) ∨ (¬ q)
= (p) ∨ (¬ q) {Using double negation rule}
= (¬ q) ∨ (p) (it is equivalent to statement (iii))
= (q) → (p) { since x → y = ¬ (x) ∨ y }
(it is equivalent to statement (ii))

So, option (D) is correct.

Quiz of this Question

Attention reader! Don’t stop learning now. Learn all GATE CS concepts with Free Live Classes on our youtube channel.

My Personal Notes arrow_drop_up
Recommended Articles
Page :